Genetic control of a structural polymer of the Neurospora crassa cell wall. - Silva, M (1984)
The heteropolysaccharide present in fraction 1 of the Neurospora crassa cell wall has been characterized in wild-type and morphological mutant strains of this fungus. Single and double mutations have been studied to determine possible genetic interactions controlling the chemical composition of such heteropolysaccharides . Single mutations studied were peak-2, scumbo ( FGSC 49), ragged ( FGSC 296), and crisp -1 ( FGSC 488). Double mutations studied were peak-2, scumbo ( FGSC 419), and ragged crisp -1. In all these strains, the main constituents of the heteropolysaccharide were glucose, mannose and galactose. Glycosidic linkages binding these neutral sugars have been identified by gas-liquid chromatography. A chemical structure of fraction I heteropolysaccharide is proposed. The results obtained with double mutants suggest the existence of genetic interactions, such as complementation or additive effects of lesions of different genes, to control the chemical composition and structure of the cell wall and the morphology of N. crassa mycelium.